Dynamics Modeling and Analysis of a 3-PPR Parallel Mechanism - Xie Zhijiang; Wu Xiaoyong; Zhang Jun; Pang Zhi; Sun Qi (Jixie chuandong)
Based on the homogeneous coordinate transformation principle,the integrated inverse kinematics of the 3-PPR parallel mechanism is established,and the first-order coefficient method is applied to work out its Jacobian matrix. The rigid-body dynamics model is derived by using the Lagrange equation. Comparing the rigid-body dynamics simulation results under the typical working condition separately obtained by ADAMS and Matlab,the validity of theoretical analysis is verified. Then the flexible dynamics simulation is conducted by combining ANSYS and ADAMS,which forms the foundation of complete dynamics analysis. The research provides necessary information for dynamic performance analysis,control of the system and error analysis of the parallel mechanism,it also can be used to deal with the dynamics problem of similar parallel mechanisms.